Alzheimer's Disease Staging and Prediction - Liu, Sidong (Multimodal Neuroimaging Computing for the Characterization of Neurodegenerative Disorders, 2017)
Alzheimer’s disease (AD), one of the most common and disabling neurodegenerative disorders among aging people, accounts for nearly 70% of all dementia cases.